Correction to: Which Subjective Expectations Explain Asset Prices? (Review of Financial Studies, 2025)
This is a correction to: Ricardo Delao, Sean Myers, Which Subjective Expectations Explain Asset Prices? The Review of Financial Studies, Volume 37, Issue 6, June 2024, Pages 1929–1978, https://doi.org/10.1093/rfs/hhae009In the originally published version of this manuscript, author, Ricardo Delao’s, surname was misspelled.This error has been corrected.